DAMPAK ALIH FUNGSI LAHAN PERSAWAHAN TERHADAP PRODUKSI BERAS DALAM RANGKA KETAHANAN PANGAN (STUDI KASUS DI KABUPATEN TANGERANG) - Karini, Dyah May (Jurnal Ketahanan Nasional, 2013)
This paper explained paddy fields conversion at Tangerang Regency which enhancing every year. The quantitative data showed the paddy fields conversion was affected with economic structure change and the infrastructure facilities enhancement and also the high population growth. Real paddy fields area affected the total paddy production enhancement, however the width of paddy fields conversion to non-paddy fields had not yet proven affected the total paddy production decrease at Tangerang Regency if it was supported with agricultural technology and intensification. The Tangerang Regency communityâs need on rice was yet lacking, Tangerang Regional Government has to bring rice from other region to fulfill this need.Keywords: Field Conversion, Paddy Field, Rice Production, and Food Resilience.